2011
DOI: 10.1093/icvts/ivr085
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplant for interstitial lung disease: outcomes for single versus bilateral lung transplantation

Abstract: This study was undertaken to evaluate outcomes for single (SLT) vs. bilateral lung transplantation (BLT) in patients with interstitial lung disease (ILD). One hundred and eleven patients with ILD who underwent lung transplantation between January 1993 and March 2009 were evaluated. Recipients with BLT were younger (43 ± 12 vs. 57 ± 7 years), and significantly more patients with non-idiopathic pulmonary fibrosis (IPF) received BLT (50%) vs. patients with IPF (18%). BLT recipients had a significantly longer mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 16 publications
1
37
1
4
Order By: Relevance
“…The primary definition of grade 3 PGD at 48 or 72 hours after transplant was associated with a relative risk (RR) of 4.8 (95% CI, 3.3-7.0; P , 0.001) for death within 90 days of transplant compared with those without grade 3 PGD and an ARI of 18% (95% CI, 12-24). Grade 3 PGD was associated with a significantly increased 1-year mortality (RR, 3.0; 95% CI, 2.3-3.9; P , 0.001) compared with those without grade 3 PGD, and an ARI of 23% (95% CI, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Although the magnitude of the association between grade 3 PGD and mortality was attenuated when the alternate definition of any grade 3 PGD within 72 hours was used in the sensitivity analyses, the association remained significant at 90 days (RR, 3.5; 95% CI, 2.3-5.1; P , 0.001) and 1 year (RR, 2.5; 95% CI, 1.9-3.3; P , 0.001) (see Table E6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary definition of grade 3 PGD at 48 or 72 hours after transplant was associated with a relative risk (RR) of 4.8 (95% CI, 3.3-7.0; P , 0.001) for death within 90 days of transplant compared with those without grade 3 PGD and an ARI of 18% (95% CI, 12-24). Grade 3 PGD was associated with a significantly increased 1-year mortality (RR, 3.0; 95% CI, 2.3-3.9; P , 0.001) compared with those without grade 3 PGD, and an ARI of 23% (95% CI, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Although the magnitude of the association between grade 3 PGD and mortality was attenuated when the alternate definition of any grade 3 PGD within 72 hours was used in the sensitivity analyses, the association remained significant at 90 days (RR, 3.5; 95% CI, 2.3-5.1; P , 0.001) and 1 year (RR, 2.5; 95% CI, 1.9-3.3; P , 0.001) (see Table E6).…”
Section: Resultsmentioning
confidence: 99%
“…Potential risk factors for grade 3 PGD previously identified in the literature or with hypothetical clinical or biologic plausibility were selected for analysis a priori (5)(6)(7)(14)(15)(16)(17)(18)(19)(20). Details of covariate definitions are included in the online supplement.…”
Section: Candidate Risk Factor Selection and Definitionmentioning
confidence: 99%
“…8,11 Another previous study showed that outcomes in patients who had interstitial lung disease were comparable or better with single than bilateral lung transplant, and short-and long-term survival were not significantly different for the 2 types of procedures. 15 The findings based on United Network for Organ Sharing data showed that bilateral lung transplant had significantly better survival than single lung transplant. 3 The present study did not confirm a significant effect of type of transplant on survival that was previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we have observed that following the implementation of the LAS at our institution, patients with the transplant indication of IPF were significantly older, had increased supplemental oxygen requirements, a lower cardiac index, and more comorbidities [26]. However, despite the increased disease severity and strong association of significant Group 3 PH with IPF, long-term recipient outcomes have not been significantly compromised for our patients with a pre-transplant diagnosis of pulmonary fibrosis [27].…”
Section: Discussionmentioning
confidence: 80%